Artificial Intelligence: A New Tactic to Perform Banking Operations - Saxena, Archana B; Aggarwal, Deepshikha; Sharma, Deepti (Business, Management and Economics: Research Progress Vol. 5, 2024)
Since the existence of banking culture in India around 1770 (Pre-independence phase) the bank has evolved as per the trends that exist in that era. From the Pre-independence phase to the nationalisation phase (1969) and then to the Liberalisation phase (1990 onwards) and now the digitization phase (from the last few decades). Banks have implemented changes in their working mechanism very gracefully. The most recent is the digitization phase: where only banking internal work was digitized and human power was not replaced but literate to complete their operations through machine support more efficiently in less latency. During the internet boom era, when the WWW cloud covered the industries with its thick sheet of benefits, the banking sector opted for digitizing all its records and allowing access to its customers through login details. In the current technology trends, AI (Artificial Intelligence) is ruling the tech world and banking is no less than any industry in adopting this latest technology trend. Artificial intelligence is not only simplifying processes and increasing revenue but also improving business results and increasing customer satisfaction. To achieve AI’s contribution in the banking sector, authors have worked to enlist AI algorithm’s contribution and association with various banking operations/services.